Effects of discovery learning on year two pupils’ achievement in learning fractions - Ong, Pei Wen; Chew, Cheng Meng (Penerbit Universiti Kebangsaan Malaysia, 2021)
Understanding fractions is one of the important skills that need to be developed in Mathematics curriculum as it is essential for understanding algebra, geometry as well as other aspects of Mathematics. However, pupils around the world face difficulties in learning fractions. This quasi-experimental study examined the effects of Discovery Learning on pupils’ achievement in fractions. 66 Year Two primary school pupils in Kedah were assigned into experimental (Discovery learning) and control (conventional instruction) groups. Data was collected using pre-test and post-test. Independent samples t-test and paired-samples t-test were used to analyze the data. Results indicated that: 1) there is no significant difference in pupils’ achievement in fractions (pre-test) between the groups; 2) there is a significant difference in pupils’ achievement in fractions (post-test) between the groups; 3) there is a significant difference in pupils’ achievement in fractions between the pre-test and post-test of the experimental group; and 4) there is a significant difference in Year Two pupils’ achievement in fractions between the pre-test and post-test of the control group. This concludes that Discovery Learning was effective in improving Year Two pupils’ achievement in learning fractions. Therefore, it can play a role as a starting milestone for educators in Malaysia to implement Discovery Learning in daily teaching life especially in fractions.